PERENCANAAN PRODUKSI KERUPUK MENGGUNAKAN METODE AGGREGATE PLANNING DI PABRIK UD. ABADI - Hurun 'in; Wahyu Sidiq Saputra; Ermayana Megawati; Yogo Prasojo (JERA : Journal of Engineering Research and Application, 2023)
Abadi factory is a home industry scale factory that has not implemented planning methods in production activities, so that often the stock of crackers made is less than demand or exceeds demand which causes a lot of stock of crackers to pile up in the warehouse. In order for factories to meet stock of goods whose capacity remains in accordance with needs and reduce financial losses, it is necessary to conduct research starting from collecting data on demand, number of employees, working hours, and costs incurred for production purposes. This study uses forecasting methods, namely moving average, and exponential smoothing, in analyzing the forecasting of cracker product sales. Then determine the best forecasting method from several existing methods and then determine the production planning of crackers using the aggregate planning method of labor control. Based on the data collection, processing, and analysis, the results of the aggregate planning using the labor control method for the next 3 months obtained the results of Rp. 145,000,434.76,- with a total production of 8,637 packs. Keyword : Production, Forcasting, Aggregate Planning